2020
DOI: 10.1111/ijcp.13905
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life assessment of chronic obstructive pulmonary disease patient performance with different inhalers

Abstract: Purpose This study aimed to evaluate handling of six common inhalers and to determine correlations between correct inhaler technique and patient demographics/ clinical variables. Methods A total of 180 chronic obstructive pulmonary disease (COPD) patients were crossed‐over to handle their past‐experienced inhalers among (pMDI, Aerolizer, Handihaler, Breezhaler, Turbohaler, and Diskus) randomly, without receiving verbal or demonstrative instruction (baseline assessment). Inhaler technique was assessed using pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
10
1
Order By: Relevance
“…3 Also, Respimat and pMDIs are not breath-actuated like DPIs; they require additional patient skills and coordination to initiate the drug delivery which was an obstacle in the majority of the elderly population being elderly with multiple comorbidities hindering their physical capabilities with poor hand-lung coordination. 32,34,37,57 The incidence of incorrect technique was lower with pMDI compared with Respimat (93.33% vs 100%, respectively), unlike previous reports, 3,20 because of differences in past-experience of our study participants with pMDIs Vs. Respimat (75% vs 0%, respectively). Our data emphasise that a proper use of one inhaler is not necessarily translated into…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…3 Also, Respimat and pMDIs are not breath-actuated like DPIs; they require additional patient skills and coordination to initiate the drug delivery which was an obstacle in the majority of the elderly population being elderly with multiple comorbidities hindering their physical capabilities with poor hand-lung coordination. 32,34,37,57 The incidence of incorrect technique was lower with pMDI compared with Respimat (93.33% vs 100%, respectively), unlike previous reports, 3,20 because of differences in past-experience of our study participants with pMDIs Vs. Respimat (75% vs 0%, respectively). Our data emphasise that a proper use of one inhaler is not necessarily translated into…”
Section: Discussioncontrasting
confidence: 64%
“…62 Subject education and training on correct inhaler technique significantly improves their skills for all inhalers, repeated counselling could overcome all challenging patient-related or inhaler-related factors confirming that repeated counselling is a crucial aspect of treatment efficacy, and prescribers should repeatedly verify the patients' proficiency in the use of inhalers with a focus on the commonly reported errors (difficult steps). 3,12,20,32,[63][64][65] Finally, it was found that lack of a past-experience to inhaler was the strongest determinant of an incorrect inhaler technique followed by the type of inhaler; Respimat, Diskhaler, Discus and pMDI use are most likely leading to an incorrect inhaler technique, unlike…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…MDI inhalation technique differs very much from that of the dry powder inhaler, especially in the inhalation flow required to deliver the dose [10][11][12][13][14][15]. Incorrect utilization of inhalers can be noted between all ages of patients, but it appears more frequently within children and older patients [16][17][18][19].Some previous studies have shown that most repeated inhalation technique mistakes were the inability in actuation coordination of MDI at the time of inhalation, maintaining the needed inhalation flow for a sufficient period, the period of holding the breath after inhalation is shorter than recommended, and missing shaking of the MDI before use to mix the contents [20][21][22][23]. The patient's ability to inhale the aerosolized drug deeply and steadily for 5 s is a key step in the inhalation process, as faster inhalation speed will decrease the portion of drug delivered to the lungs, which leads to poor asthma control [21,24].…”
Section: Introductionmentioning
confidence: 99%